2004
DOI: 10.1128/jb.186.3.889-893.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vibrio vulnificus Capsular Polysaccharide Inhibits Biofilm Formation

Abstract: Vibrio vulnificus is a human pathogen that produces lethal septicemia in susceptible persons, and the primary virulence factor for this organism is capsular polysaccharide (CPS). The role of the capsule in V. vulnificus biofilms was examined under a variety of conditions, by using either defined CPS mutants or spontaneous CPS expression phase variants derived from multiple strains. CPS expression was shown to inhibit attachment and biofilm formation, which contrasted with other studies describing polysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 45 publications
12
95
3
1
Order By: Relevance
“…OP strains of V. vulnificus also produce a capsule, and this capsule is known to confer virulence (Yoshida et al, 1985;Simpson et al, 1987;Wright et al, 1999). These opacity-determining capsules of V. cholerae O-139 and V. vulnificus interfere with biofilm formation (Kierek and Watnick, 2003a,b;Joseph and Wright, 2004). V. cholerae strains (O139 as well as O1) also produce another form of extracellular polysaccharide, designated VPS.…”
Section: Discussionmentioning
confidence: 99%
“…OP strains of V. vulnificus also produce a capsule, and this capsule is known to confer virulence (Yoshida et al, 1985;Simpson et al, 1987;Wright et al, 1999). These opacity-determining capsules of V. cholerae O-139 and V. vulnificus interfere with biofilm formation (Kierek and Watnick, 2003a,b;Joseph and Wright, 2004). V. cholerae strains (O139 as well as O1) also produce another form of extracellular polysaccharide, designated VPS.…”
Section: Discussionmentioning
confidence: 99%
“…appear to have negative roles. For example, loss of the group 1 capsular polysaccharide (CPS) in V. vulnificus is associated with increased attachment and, subsequently, reduced biofilm formation (23,73). V. cholerae O139 contains a locus with genes for CPS and lipopolysaccharide (LPS) O antigen biosynthesis that also plays a negative role in biofilm formation (77).…”
Section: Figmentioning
confidence: 99%
“…When the autoagglutination activities of NY018 and the wild type were compared according to the procedures of Misawa and Blaser (22), the mutant was not as agglutinating as the wild type, indicating that the impaired adherence exhibited by the wbpP mutant might be related to its decreased autoagglutination activity (data not shown). However, it has recently been observed that the production of CPS and the ability of V. vulnificus to form a biofilm on abiotic surfaces are inversely related (12). This suggests that the correlation between CPS and V. vulnificus adhesion may vary with complex parameters that still remain to be determined.…”
Section: Wbpp Is Required For Adhesion To Epithelial Cells In Vitromentioning
confidence: 99%